Interaction of Antistasin-Related Peptides with Factor Xa: Identification of a Core Inhibitory Sequence - Ohta, Noriya; Brush, Michael; Jacobs, John W (Thrombosis and Haemostasis, 1994)
Antistasin, isolated from the Mexican leech, is a 119 amino acid protein which is a selective and potent inhibitor of coagulation Factor Xa. Previous studies indicated that an arginine residue located at position 34 of the inhibitor was cleaved by Factor Xa during the inhibition reaction. To evaluate this residue as the reactive site of antistasin, and to define shorter fragments of antistasin displaying Factor Xa-inhibitory activity, a series of peptides were synthesized corresponding to amino acids 27- 49 of the inhibitor. The most potent peptide synthesized was a disulfide-bridged, 19 amino acid peptide, ATS29-47, which inhibited Factor Xa with a Ki = 35 nM, and increased plasma clotting times by over 4-fold at a concentration of 33 uM. Reduction or sulfation of the cysteine residues in ATS29-47 reduced Factor Xa inhibitory activity by over 95%. Peptides as short as seven residues corresponding to position 33-39 of antistasin displayed Factor Xa inhibitory activity. The peptides did not inhibit thrombin or trypsin at concentrations 1000-fold higher than used in Factor Xa assays. The shortest peptide displaying anticoagulant activity in human plasma was the disulfide-bridged peptide, D-Arg-Cys-Arg-Val-His-Cys-Pro, which increased clotting times by 50% at micromolar concentrations. These results demonstrate that antistasin-related peptide sequences can serve as model structures for the development of novel, low molecular weight anticoagulants.